The protective effect of natural medicines against excessive inflammation and oxidative stress in acute lung injury by regulating the Nrf2 signaling pathway - Luan, Rumei; Ding, Dongyan; Yang, Junling (Frontiers in Pharmacology, 2022)
Acute lung injury (ALI) is a common critical disease of the respiratory system that progresses into acute respiratory distress syndrome (ARDS), with high mortality, mainly related to pulmonary oxidative stress imbalance and severe inflammation. However, there are no clear and effective treatment strategies at present. Nuclear factor erythroid 2-related factor 2（Nrf2）is a transcription factor that interacts with multiple signaling pathways and regulates the activity of multiple oxidases (NOX, NOS, XO, CYP) related to inflammation and apoptosis, and exhibits antioxidant and anti-inflammatory roles in ALI. Recently, several studies have reported that the active ingredients of natural medicines show protective effects on ALI via the Nrf2 signaling pathway. In addition, they are cheap, naturally available, and possess minimal toxicity, thereby having good clinical research and application value. Herein, we summarized various studies on the protective effects of natural pharmaceutical components such as polyphenols, flavonoids, terpenoids, alkaloids, and polysaccharides on ALI through the Nrf2 signaling pathway and demonstrated existing gaps as well as future perspectives.